Reading Habits From the Perspective of Diverse Socioeconomic Status - Hani Holidiya (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
Reading has been recognized as one of the essential skills that everyone in the world should have. Someone's ability to understand a text determines the next steps they take, such as decision-making, problem-solving, or retelling the ideas of the text. Students with a high interest in reading, meaning those with good reading habits, tend to achieve a higher score than those who do not (Le et al., 2019). In the young learner context, Hung and Marjoribanks (as cited in Yusof, 2010) stated that children’s success in learning certain positive behaviors, such as reading habits, is significantly influenced by several factors including family background. Chakravarthy (as cited in Yusof, 2010) believed that family socioeconomic status, lifestyle, and relationships between parents and children at home would all significantly impact the development of reading habits and interests.
Reuploud file repositori 28 Januari 2026_Yudi
Keywords: Reading Habits; Perspective of Diverse Socioeconomic Status